2021
DOI: 10.2214/ajr.21.25584
|View full text |Cite
|
Sign up to set email alerts
|

Conventional-Dose CT Versus 2-mSv CT for Right Colonic Diverticulitis as an Alternate Diagnosis of Appendicitis: Secondary Analysis of Large Pragmatic Randomized Trial Data

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A post hoc analysis [ 84 ] of the Korean multi-center trial data [ 43 ] suggested that 2-mSv CT is comparable to CDCT (≤ 8 mSv) for the diagnosis of right colonic diverticulitis, which is the most common specific alternative diagnosis in South Korea [ 41 43 ], and probably in Eastern Asia. Other data also indirectly support the idea that LDCT also works well for alternative diagnoses.…”
Section: Diagnostic Effectiveness and Efficacy: Ldct Vs Cdctmentioning
confidence: 99%
“…A post hoc analysis [ 84 ] of the Korean multi-center trial data [ 43 ] suggested that 2-mSv CT is comparable to CDCT (≤ 8 mSv) for the diagnosis of right colonic diverticulitis, which is the most common specific alternative diagnosis in South Korea [ 41 43 ], and probably in Eastern Asia. Other data also indirectly support the idea that LDCT also works well for alternative diagnoses.…”
Section: Diagnostic Effectiveness and Efficacy: Ldct Vs Cdctmentioning
confidence: 99%